STRATEGI PENINGKATAN PROFESIONALISME PRAKTISI BAITUL MAAL WAT TAMWIL (BMT) DI KABUPATEN BANYUMAS - Karsidi Karsidi; Rahab Rahab; Rasyid Mei Mustafa (Performance: Jurnal Personalia, Financial, Operasional, Marketing dan Sistem Informasi, 2011)
This research aimed to know determinate factors that support the professionalism of BMT people in Banyumas regency and develop some strategies to improve profesionlism of BMT people. The type of the research is the qualitative which collected the data with questioner, depth interview and library research. As the qualitative research, the analysis data acted simultaneous with collecting the data, interpretation, and writing the research result. The results of this research are: Firstly, the interpretation of professionalism by many BMT people tends practically. The professionalism explained in the context of service quality given by BMT to its customers. Mean, the biggest professionalism measure is in service quality. Secondly, there are some influenced factors toward the professionalism of BMT people, namely: (1) Understanding to the concept of Syariah finance concept; (2). The operational obstacle in Syariah finance system; (3). The human resources management (about the role and the function); (4) The Performance of BMT among the banking business competition; (5) The unbalance between saving and cost; (6) The loss profit sharing for the customers; and (7) the Mudharabah which is not become the priority of BMT.Internal and external component very important to improve professionalism BMT people.